PELATIHAN SABLON DENGAN TEKNIK COLET CRAYON BAGI SISWA BERKEBUTUHAN KHUSUS DI SLB BINA KARYA INSANI KARANGANYAR - Syafi’i, Achmad (Acintya, 2017)
Screen printing businesses still had great opportunities to serve as potential entrepreneurial activities. The purpose of screening training with colet crayon technique to students with special needs(disabled) in SMPLB and SMALB Bina Karya Insani was to prepare the skills of SLB students in orderto gain recognition and be able to be independent in society besides could be used for entrepreneurship. Activities that were carried out involving 40 studentsof Deaf-Speech impaired (B-class) andMentally Disables (C-class). The execution technique used brainstorming method and the method ofspecial classroom action techniques. The brainstorming method was used so that the active workshopparticipants expended their ideas in the form of visual design to be transferred on paper throughscreen printing with colet crayon technique. While the specific classroom action method was meant,was a persuasive approach, because people with special needs required more attention. So with theindividual approach in fishing ideas and their imagination, students were expected to be honed andwell developed.Keywords: colet crayon, screen printing, special need students.